Maximizing the Use of Ivermectin Transethosomal Cream in the Treatment of Scabies - Mohammad H. Alyami; Hamad S. Alyami; Asmaa M. Abdo; Shereen A. Sabry; Hanan M. El-Nahas; Margrit M. Ayoub (MDPI AG, 2024)
In an effort to tackle the skin reactions frequently observed with topical application of ivermectin (IVM), a study was conducted to develop and optimize transethosomes (TESMs) loaded with IVM for scabies treatment. A three-factor, two-level (23) full factorial design was employed. Soyabean phosphatidylcholine concentration (A), ethanol concentration (B) and Span 60 amount (C) were studied as independent factors, while entrapment efficiency (EE), particle size (PS), polydispersity index (PDI), zeta potential (ZP) and drug release after 6 h (Q6h) were characterized. The skin sensitivity of the optimized formulation was evaluated by skin irritation test and histopathological examination. The EE% ranged from 88.55 ± 0.576% to 94.13 ± 0.305%, PS was from 318.033 ± 45.61 nm to 561.400 ± 45.17 nm, PDI was from 0.328 ± 0.139 to 0.671 ± 0.103, ZP was from −54.13 ± 1.09 mV to −60.50 ± 2.34 mV and Q6h was from 66.20 ± 0.30% to 93.46 ± 0.86%. The IVM-loaded transethosomal cream showed lower skin irritation and a more intact epidermal layer with intact keratinocyte, compared to the marketed cream which showed severe destruction of the keratin layer. Therefore, patient compliance can be improved by encapsulating IVM within TESMs to minimize its skin reactions.